Periosteal matrix-derived hydrogel promotes bone repair through an early immune regulation coupled with enhanced angio- and osteogenesis. (January 2020) - Qiu, Pengcheng; Li, Mobai; Chen, Kai; Fang, Bin; Chen, Pengfei; Tang, Zhibin; Lin, Xianfeng; Fan, Shunwu
Abstract: Bone healing is a complex physiological process initiated by early regulation of the inflammatory immunity and entails multiple events including angiogenesis, osteogenic differentiation, and biomineralization. Here, we fabricated an injectable periosteal extracellular matrix (PEM) hydrogel that dynamically integrates multiple biological functions and, therefore, acts at different stages of the fracture healing process. PEM hydrogels were fully characterized compared with a collagen I hydrogel. The effects of PEM hydrogels on the different phases of the healing process were assessed in vitro . PEM hydrogels induced the recruitment and M2-polarization of macrophages, promoted the differentiation of MSCs into endothelial-like cells, HUVEC tube formation, osteogenic differentiation of primary calvarial osteoblasts and MSCs, and mineralization after being immersed in simulated body fluid. The dynamic and multiphase effects of the hydrogels were evaluated using a rat critical-sized calvarial defect model in vivo . During the early phase of repair, PEM hydrogels facilitated the M1-to-M2 transition of macrophages. As bone repair progressed, PEM hydrogels promoted blood vessel migration, the development of relative larger blood vessels, and functional vascularization. These effects were also verified in a subcutaneous embedding model. Eventually, PEM hydrogels promoted mature bone formation in large bone defects to a greater extent than collagen I hydrogels. These biological effects coordinated well with the natural process of bone regeneration. Thus, PEM hydrogels may serve as promising biomaterials in bone tissue engineering. Highlights: Prolonged M1 phase and an M2 transformation failure occur in critical size bone defects. PEM hydrogels participate in early immune regulation of bone repair and promotes M1-to-M2 transition of macrophages. PEM hydrogels play a promoting role in the process angiogenesis and osteogenic differentiation of bone repair. PEM hydrogels coordinate and guide several overlapping bone regeneration events. PEM hydrogels showed superior bone healing properties.